Motorola Xoom the missing manual - Gralla, Preston (O'Reilly, 2011)
Looks at the features and functions of the Motorola Xoom, covering such topics as accessing the Internet, setting up an email account, using apps, playing games, playing and managing music, watching videos, and more.
Print version record
Keywords: Xoom (Computer); Tablet computers; Xoom (Ordinateur); Tablettes électroniques; COMPUTERS; Hardware; Handheld Devices